Plasma concentrations of carotenoids and vitamin C are better correlated with dietary intake in normal weight than overweight and obese elderly subjects - Vioque, Jesús; Weinbrenner, Tanja; Asensio, Laura; Castelló, Adela; Young, Ian S.; Fletcher, Astrid (British journal of nutrition, 2007)
Carotenoid and vitamin C intakes, assessed by FFQ, have been positively associated with plasma concentrations in different populations. However, the influence of BMI on these associations has not been explored in detail. We explored in a cross-sectional study the relation between dietary carotenoid and vitamin C intakes, using a 135-item FFQ, with their plasma concentrations by BMI categories in 252 men and 293 women, 65 years and older. For men and women combined, significant (P < 0·05) Pearson correlations were observed between energy-adjusted dietary intakes and plasma concentrations (carotenoids adjusted for cholesterol) for: α-carotene 0·21, β-carotene 0·19, lycopene 0·18, β-cryptoxanthin 0·20 and vitamin C 0·36. Multiple linear regression analyses showed that the intake of carotenoids and vitamin C were significant predictors of their respective plasma concentration (P < 0·01), and that BMI was inversely associated with plasma concentration of carotenoids (P ≤ 0·01) but not with plasma vitamin C. In addition, we observed significant interactions between BMI and the intakes of α-carotene and lutein + zeaxanthin, and to a lower extent β-carotene, suggesting that these intakes in subjects with high BMI were not good predictors of their plasma concentration. The present data suggest that plasma carotenoids and vitamin C may be good markers of dietary intake in elderly subjects, but not so for α-carotene, β-carotene and lutein + zeaxanthin in obese subjects.